Transgender Medicine and Risk of Venous Thromboembolism - Bunderen, C.C. Van; Leentjens, J.; Middeldorp, S. (Hämostaseologie, 2022)
Gender dysphoria refers to psychological distress that results from an incongruence between gender identity and sex assigned at birth. Administration of sex hormones is most often used as a first step to develop and maintain physical characteristics consistent with gender identity. Gender-affirming hormone treatment is considered beneficial for the quality of life and reduction of depression. However, estrogen and androgen-lowering hormone therapies used in transwomen are in particular associated with increased risk of venous thromboembolism. In this review, introduced by a clinical case, we provide an overview of the currently available medical therapies in transgender medicine, and put the associated increased risk of venous thromboembolism into perspective.
Keywords: transgender; hormone replacement therapy; venous thromboembolism; venous thrombosis; pulmonary embolism